2019
DOI: 10.1177/0890117118816750c
|View full text |Cite
|
Sign up to set email alerts
|

Worksite Policies for Promoting Physical Activity

Abstract: function is improved. For survivors of colorectal, breast, and prostate cancer, greater amounts of physical activity reduce risk of reoccurrence of the original cancer. For those with hypertension, physical activity reduces progression of the disease. Given that many employees are managing chronic conditions, physical activity has a great potential to enhance worker performance and reduce health-care costs in those who are afflicted with these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In the evolving work landscape, Table 2 provides examples of both public policy levers and organizational level solutions to promote [39][40][41][42][43][44][45][46] Public Policy Levers • Offer tax incentives for employers who provide subsidies for active transportation/use of public transportation to work, memberships to recreational/fitness facilities, and/or supervised exercise prescription with a health and fitness professional • Allow health savings accounts/flexible spending accounts to cover physical activity-related expenses (eg, pass legislation similar to Personal Health Investment Today Act) • Make grants available to employers (especially small-mid-size employers) to offset costs of wellness and physical activity programming • Fund for complete streets policies and other active living infrastructure and connectivity in community design • Standardize and implement performance and quality measures for physical activity assessment, prescription, and referral in health care delivery with state and federal regulation and public and private health care plans • Create appropriations for training in physical activity promotion across multiple professions • Organizational-level strategies • Provide subsidies for memberships to health and fitness clubs, parks, and other community recreational facilities, and/or for supervised exercise prescriptions with a health-and-fitness professional (facilitated through local partnerships) • Offer paid time to be physically active during the workday. Encourage short activity breaks or active meetings that provide opportunities for employees to break up sitting time (by standing or moving, especially for meetings >1 hour) • Encourage stretching before, after, and/or during shifts, especially with employees doing manual labor to decrease the risk of musculoskeletal injury or pain • Offer flex-time policy to allow employees to shift their work schedules to incorporate physical activity into the workday • Implement an active meeting policy that encourages movement throughout meetings • Offer employees opportunities to wear casual, workout-friendly attire • Encourage individual worksite behaviors that allow for additional movement, less sitting time:…”
Section: Potential Solutions For Integrating Physical Activity Promot...mentioning
confidence: 99%
“…In the evolving work landscape, Table 2 provides examples of both public policy levers and organizational level solutions to promote [39][40][41][42][43][44][45][46] Public Policy Levers • Offer tax incentives for employers who provide subsidies for active transportation/use of public transportation to work, memberships to recreational/fitness facilities, and/or supervised exercise prescription with a health and fitness professional • Allow health savings accounts/flexible spending accounts to cover physical activity-related expenses (eg, pass legislation similar to Personal Health Investment Today Act) • Make grants available to employers (especially small-mid-size employers) to offset costs of wellness and physical activity programming • Fund for complete streets policies and other active living infrastructure and connectivity in community design • Standardize and implement performance and quality measures for physical activity assessment, prescription, and referral in health care delivery with state and federal regulation and public and private health care plans • Create appropriations for training in physical activity promotion across multiple professions • Organizational-level strategies • Provide subsidies for memberships to health and fitness clubs, parks, and other community recreational facilities, and/or for supervised exercise prescriptions with a health-and-fitness professional (facilitated through local partnerships) • Offer paid time to be physically active during the workday. Encourage short activity breaks or active meetings that provide opportunities for employees to break up sitting time (by standing or moving, especially for meetings >1 hour) • Encourage stretching before, after, and/or during shifts, especially with employees doing manual labor to decrease the risk of musculoskeletal injury or pain • Offer flex-time policy to allow employees to shift their work schedules to incorporate physical activity into the workday • Implement an active meeting policy that encourages movement throughout meetings • Offer employees opportunities to wear casual, workout-friendly attire • Encourage individual worksite behaviors that allow for additional movement, less sitting time:…”
Section: Potential Solutions For Integrating Physical Activity Promot...mentioning
confidence: 99%
“…Ablah and coworkers (17) reported that policy initiatives may be used to create a workplace culture where being active is the norm. Leveraging public policy along with written policies that may be implemented at individual worksites may be particularly powerful because it connects directly to places beyond the worksite that are more proximal to where workers and their families live, play, learn, and worship, thereby integrating such levers into other parts of their lives (18). Table 3 presents examples of public policies as well as organizational policies that support physical activity.…”
Section: Policy Supports For Physical Activity At the Workplacementioning
confidence: 99%
“…For more information on this topic, see Hipp et al (8), Pronk and Kottke (16), Ablah et al (18), and Pronk et al (19)…”
Section: Policy Supports For Physical Activity At the Workplacementioning
confidence: 99%
“…Strategies for encouraging active workplaces include active workstations, portable exercise machines, PA breaks, prompting software, and skip-stop elevator use (Pronk, 2022). Examples of workplace policies supporting PA include active meetings (e.g., walking, standing, moving, and stretching), allowing 10 to 15 minutes per day allocated either as intentional activity while on the clock or a movement break at a specified time and location, flextime to incorporate PA into workday, subsides for active commuting, and promoting walkable locations around the worksite (Ablah et al, 2019). The 2018 Physical Activity Guidelines Advisory Committee (PAGAC, 2018) found strong support for using wearable devices, web-based interventions, and mobile phone strategies in worksite PA interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Incidental PA and increasing the number of steps taken during the day could be a viable means to enhance cardiorespiratory fitness, decrease sedentary time, and lower all-cause mortality (Forberger et al, 2022; Saint-Maurice et al, 2020). Inexpensive innovations that call for policies that support OPA, including scheduled movement breaks, stair prompts, and routinized stretching have been suggested (Ablah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%